Assessment of aerosol radiation environment in short-range region of ChNPP during building of the new safe confinement - Garger, E.K.; Shynkarenko, V.K.; Kashpur, V.A.; Skorjak, G.G.; Kalinovsky, A.K. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Variability of ¹³⁷Cs volume activity in a subsurface layer of the atmosphere of a short-range region of the object "Shelter" (object "Ukryttya") during the works on building of a new safety confinement in 2016 was investigated. Influence of the type and location of works, weather conditions, and sampling points was shown. Excess of medial permissible concentrations of ¹³⁷Cs in the air was not fixed during the observations. However, due to the averaging of the measured values of the volume activity for the exposure time of the filter and use of the stationary aerosol samplers, it cannot ensure the absence of excess of the permissible concentrations at the locations of works and on the propagation path of the local emission plumes. In 2016, as well as in 2013 - 2015, high levels of ¹³⁷Cs volume activity in the air were preferentially localized near to the machine hall of the 4th block and near to the places of ground works at the industrial site [ 1]. Concurrently the levels of volume activity essentially grew (practically by the order of magnitude) due to the intense works on the machine hall transformation. The conservative estimation of volume activity of isotopes of the plutonium, executed in the assumption of fuel composition of hot particles, showed the presence of substantial excess of permissible limits even for the average values within, at least, four weeks. Absence of reliable correlation (R = -0.09) of ¹³⁷Cs volume activity in the air near to the machine hall and near to the aerosol sampler 1,4 km remote from it testifies the localization of pollution within the industrial site. Досліджено мінливість об'ємної активності ¹³⁷Cs у приземному шарі атмосфери ближньої зони об'єкта «Укриття» під час проведення робіт зі спорудження нового безпечного конфайнмента у 2016 р. Продемонстровано вплив виду та місця проведення робіт, метеорологічних умов, а також місця відбору проб. За час спостережень не зафіксовано перевищення середніх допустимих концентрацій ¹³⁷Cs в повітрі. Однак унаслідок усереднення виміряних значень об'ємної активності за часом експозиції фільтра та використання стаціонарних пробовідбірників даний факт не може гарантувати відсутність перевищень у місцях проведення робіт і по шляху поширення факелів локальних викидів. У 2016 р., як і в 2013 - 2015 рр., високі рівні об'ємної активності ¹³⁷Cs в повітрі були переважно локалізовані поблизу машинного залу 4-го блока та біля місць проведення земляних робіт на промисловому майданчику [1]. При цьому самі рівні об'ємної активності істотно зросли (практично на порядок) у зв'язку з інтенсивними роботами по трансформації машинного залу. Консервативна оцінка об'ємної активності ізотопів плутонію, виконана у припущенні паливного складу гарячих частинок, показала наявність істотних перевищень допустимих рівнів навіть для усереднених величин, у крайньому випадку, протягом чотирьох тижнів. Відсутність достовірної кореляції об'ємної активності ¹³⁷Cs в повітрі поблизу машинного залу та біля віддаленого від нього на 1,4 км пробовідбірника (R = -0,09) свідчить про локалізацію забруднень у межах промислового майданчика. Исследована изменчивость объемной активности ¹³⁷Cs в приземном слое атмосферы ближней зоны объекта «Укрытие» во время проведения работ по сооружению нового безопасного конфайнмента в 2016 г. Продемонстрировано влияние вида и места проведения работ, метеорологических условий, а также места отбора проб. За время наблюдений не зафиксированы превышения средних допустимых концентраций ¹³⁷Cs в воздухе. Однако вследствие усреднения измеренных значений объемной активности по времени экспозиции фильтра и использования стационарных пробоотборников данный факт не может гарантировать отсутствие превышений в местах проведения работ и по пути распространения факелов локальных выбросов. В 2016 г., как и в 2013 – 2015 гг., высокие уровни объемной активности ¹³⁷Cs в воздухе были преимущественно локализованы вблизи машинного зала 4-го блока и около мест проведения земляных работ на промышленной площадке [1]. При этом сами уровни объемной активности существенно выросли (практически на порядок) в связи с интенсивными работами по преобразованию машинного зала. Консервативная оценка объемной активности изотопов плутония, выполненная в предположении топливного состава горячих частиц, показала наличие существенных превышений допустимых уровней даже для усредненных величин, по крайней мере, в течение четырех недель. Отсутствие достоверной корреляции объемной активности ¹³⁷Cs в воздухе возле машинного зала и возле удаленного от него на 1,4 км пробоотборника (R = -0,09) свидетельствует о локализации загрязнений в пределах промышленной площадки.